Mergers and acquisitions a research overview - King, David R.; Bauer, Florian; Schriber, Svante (Routledge, 2019)
The process of identifying and evaluating a target firm, completing a deal after its negotiation and announcement, and then integrating a target firm after legal combination is a multi-year process with uncertain returns to acquiring firms. Research on mergers and acquisitions (M&As) is progressing rapidly yet it remains fragmented across multiple research perspectives that largely examine different acquisition phases separately and coincide with a focus on different research variables. As a result, research fragmentation means that a researcher in one area may be unaware of research from related areas that is likely relevant. This contributes to research silos with M&A research displaying different traditions, starting points, and assumptions. Mergers and Acquisitions: A Research Overview summarizes the frontier in M&A research and provides insights into where it can be expanded. It undertakes the needed integration and reconciliation of research in order to derive practical knowledge for managing acquisitions from beginning to end, providing a summary of what is known and its implications for future research. This concise overview reconciles and integrates the state of the art in our understanding of mergers and acquisitions, providing an essential first stopping point in the research journey of students and scholars working in this area.
Includes bibliographical references (pages 70-97) and index. - Description based on print version record
Keywords: Consolidation and mergers of corporations; BUSINESS & ECONOMICS / Industrial Management; BUSINESS & ECONOMICS / Management; BUSINESS & ECONOMICS / Management Science; BUSINESS & ECONOMICS / Organizational Behavior; BUSINESS & ECONOMICS / Strategic Planning; BUSINESS & ECONOMICS / International / General; BUSINESS & ECONOMICS / General; Consolidation and merger of corporations